Financial Crises – the Product of Greed - Pakuła, Andrzej (Regional Barometer. Analyses & Prognoses, 2010)
The paper follows the course of financial crises – financial scandals over the centuries. It allows to verify the thesis, that financial crises are much the same, always underlined by greed and speculation. The successive crises are described by an even larger scale of speculation then in the past. The modern financial crisis differs from the earlier ones in all that it is global in character because of the globalization of economical, financial and social phenomena. At the same time its consequences for a real sphere are severe. The paper picked up as well the topic of the ways of preventing crises in the future.